Factibilidad para la Implementación de una Lavadora de Vehículos Livianos con Tecnología a Vapor en la Ciudad de Loja - Córdova Encalada, Diego Marx (2017)
When developing an investment plan, it is necessary to take into account the variables to evaluate, so today it is necessary to determine how convenient it is to implement an investment by estimating costs and evaluating the benefits, in order to implement a business. It is for this reason that when the idea of a service investment plan for a Light Vehicle Washer with Steam Technology arises, taking into account the real situation of the country; That is, evaluating the economy in which I am developing so as to evaluate the contribution given to it. When implementing this investment plan I focus mainly on the satisfaction of a need that in the market is not being fully covered and therefore becomes an opportunity in the short and medium term. The present Feasibility Project proposes the implementation of a Washing Services Company with Steam Technology for Light Vehicles, with the purpose of providing an innovative and environmental service with quality standards, efficient and efficient of the washing, making with the best technology available In the market, to obtain total customer satisfaction. In the first chapter, everything related to the Market Study was developed in which it was determined that 97% of the respondents accepted the implementation of a light-duty washing machine with steam technology because the existing washing machines The town does not have the necessary infrastructure to carry out such activities and much less have a waiting room for the convenience of customers, who wait around 60 minutes for their vehicle to be washed. 8 Within the second chapter that is the Technical Study we were able to determine the installed capacity of our company which is 35,040 vehicles, while for the capacity used is 8.320 vehicles washed which will cover 24% of the unsatisfied demand. I should also point out that our company will be located in the city of Loja, Tebaida Baja sector, Sucre Parish, diagonal to Coliseo City of Loja, appropriate place because it is a very busy sector and above all that has all basic services, access Easy and close to the river to get the water. As determined in the washing process and taking into consideration several points such as infrastructure and machinery could be established that the average wash time will be 30 minutes, time that is very beneficial and short, compared to different washing systems Which are developed in the locality. In dealing with the third chapter I get what concerns the Administrative and Legal Study in which one of the most relevant points is the Legal Constitution of the Company with which it is stated that the Social Name with which it will be registered with the same name ViperCar SA, was also established the different hierarchical levels with their respective manuals of functions, it was determined that the useful life of the project will have 5 years from its creation. It will be registered as a medium company and only 16 employees. As a fourth chapter, I have included what is the Financial Study, within which the different budgets with real values of the local market are developed, thus determining a total investment of $ 25,346.51, which will be covered with own capital is 71.71% and The rest with a loan in the Banco de Loja with a value of $ 10,000 representing 28.29% at an interest rate of 16% with semiannual payments for 3 years. 9 As a fifth chapter according to the Financial Assessment indicators, it was possible to determine that our VAN will be $ 165,781.65, while our TIR will be 110.5%, thus demonstrating that the project is beneficial to any investment that wishes to implement it, The RBC is US $ 1.47, which means that for every dollar invested it earns 0.47 cents, noting that the PRI investment will be recovered in an estimated 0, 9 months and 29 days, which is very Below the useful life of 5 years and the sensitivity analysis determined that the increment that can support the costs generated by the implementation of the company is 29% and the decrease it can bear in its income is 20.5% which Determines that the project is sensitive 0.987. As a final part of this thesis I have presented the corresponding conclusions and recommendations that have been obtained during the development of the same, thus giving the necessary continuity to the project and above all showing the benefits that will be provided to society.